2007
DOI: 10.1139/l07-056
|View full text |Cite
|
Sign up to set email alerts
|

Study of crumb rubber materials as paving asphalt modifiers

Abstract: Waste tire crumb rubber materials (CRM) were used to modify paving asphalts. The mixing time, hot-storage stability, Superpave grades, pumping and handling properties, phase separation tests, and repeated creep properties of the modified asphalts were studied using base asphalts of different hardness. Applying the Long-Term Pavement Performance (LTPP) program and the Transportation Association of Canada (TAC) model, optimal levels of CRM and suitable base asphalts were selected for the climatic conditions of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The use of rubber as asphalt modifier in road constructions can date back to 1960, when Charles McDonald first added crumb rubber in asphalt mixtures to improve the pavement performance [7,11,15]. During the last decades, crumb rubber modified asphalt binder has been widely used as road paving materials worldwide [20].…”
Section: Introductionmentioning
confidence: 99%
“…The use of rubber as asphalt modifier in road constructions can date back to 1960, when Charles McDonald first added crumb rubber in asphalt mixtures to improve the pavement performance [7,11,15]. During the last decades, crumb rubber modified asphalt binder has been widely used as road paving materials worldwide [20].…”
Section: Introductionmentioning
confidence: 99%
“…One solution which is being researched in order to reduce the so-called tire/road noise, is the development of more elastic surfaces to minimize the impact effect through the incorporation of crumb rubber (CR) from wasted automobile tires. In the last decades, various technical and scientific studies have reported that the addition of CR and other polymers improves mechanical properties of the road surface, such as permanent deformation, stiffness or reflective and thermal cracking [9][10][11][12][13]. Usually, the incorporation of CR as modifier of the bituminous binder, via the wet process, has reflected an improvement of the acoustic performance of the asphalt roads, obtaining a decreasing of the generated sound levels in relation to the percentage of rubber employed in the binder and/or the maximum aggregate size (macrotexture) used in the mixture [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The coarse aggregate had specific gravity of 2.65 with a maximum aggregate size of 14.6 mm. The steel cords used in this study consisted of steel wires of varying lengths (5-85 mm) and diameters of 0.2-1.3 mm with an average density of approximately 2.7 g/cm 3 , as well as rubber particle bonded to the wires. Table 2 shows the properties of recycled tire materials.…”
Section: Design and Materialsmentioning
confidence: 99%
“…Scrap tires were initially recycled for their rubber contents because of the environmental threats associated with; their proper disposal has attracted the attention of many researchers in the last years [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%